Blood gun money : how America arms gangs and cartels - Grillo, Ioan, 1973- (Bloomsbury Publishing, 2021)
Presents a searing investigation into the role of the drug trade in the black market for firearms, both within the U.S. and across the U.S.-Mexican border.